Formação continuada a distância para rede privada: análise de um curso autoinstrucional em educação especial inclusiva - Muto, Jéssica Harume Dias (Universidade Federal de São Carlos, 2025)
In recent decades, teacher training has been widely discussed in light of the technological, social, and political transformations permeating the educational field, especially given the urgency to consolidate inclusive practices in schools. The incorporation of digital technologies, particularly in continuing education, emerges as an opportunity to broaden access to knowledge. In this context, this study sought to analyze the potential and limitations of a self-instructional course mediated by digital technologies as a strategy for the continuing education of basic education teachers within the scope of inclusive education. To achieve this goal, the research unfolded into two specific objectives: (a) to characterize the pedagogical and technological proposal of the self-paced course, based on documentary analysis considering its objectives, structure, resources, and forms of didactic-methodological organization; and (b) to analyze, based on records and documents produced on the training platform, the teachers’ perceptions of the adequacy of the course content and strategies in relation to the training demands related to pedagogical practice from an inclusive perspective.Using a qualitative, descriptive, and documentary approach, this study sought to analyze documents and materials from a massive self-instructional distance learning course offered by a private company serving approximately 1,300 basic education schools nationwide through a digital platform, including quantitative and qualitative data. The analysis was organized into four axes: pedagogical and technological proposal, didactic-evaluative coherence, participants' perceptions, and formative implications. The results showed that the technology-mediated self-instructional course has the potential to contribute to the continuing education of teachers from the perspective of inclusive education, but also presents structural and pedagogical limitations that restrict its formative impact. The analysis revealed that the proposal was predominantly transmissive, focused on the provision of content, without fostering critical reflection on learning and teaching practices in the face of the real demands of inclusive schools. The results reaffirm that teacher training is a continuous and complex process that must articulate theory and practice, supported by an ethical and political commitment to school inclusion. Recognizing the limitations of the self-instructional model, the study proposes a shift in focus from simply offering courses to valuing formative experience, arguing that teacher training from the perspective of inclusive special education requires intentionality, mediation, and spaces for authorship and engagement—fundamental elements for consolidating an education committed to diversity, equity, and social participation. It concludes that continuing education mediated by digital technologies has the potential to broaden access and democratize training opportunities; however, inclusion, as a principle that implies a change in conceptions and practices, demands that teachers reflect, dialogue, and reframe their pedagogical practice. Thus, the study provides relevant insights for improving public policies, programs, and actions aimed at teacher training, contributing to the construction of more collaborative educational practices.
Online continuing teacher education in the private school sector: an analysis of a self-paced course in inclusive and special education
Keywords: Educação especial; Formação continuada de professores; Tecnologias educacionais; Inclusão escolar; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade